Parâmetros de adaptabilidade e estabilidade para produção de grãos, teores de proteínas e minerais em feijão-caupi (vigna unguiculata (l.) walp.) no semiárido brasileiro - Da Silva, Danillo Olegário Matos (2018)
The goals of this work were to compare and evaluate statistical methods of analysis of adaptability and stability for total protein, minerals and grain yield in cowpea lines, as well as retention of these nutrients after cooking to enable recommendation and registration of new cultivars for the Brazilian semiarid. Forty-four genotypes, distributed in two experiments of different population densities, were evaluated in seven environments, in the states of Bahia, Ceará, Pernambuco and Piauí. Initially, a comparison was made of ten statistical methods of adaptability and stability using only the production data. Spearman correlation coefficients were estimated between the methods. For the assessments of adaptability and stability of the genotypes the methods of Eberhart and Russell, Lin and Binns and the Model of main additive effects and multiplicative interaction - AMMI were applied. To evaluate the effect of cooking, 24 genotypes were used, including ten lines, five commercial cultivars and nine landraces maintained by farmers. The seed protein content was quantified through the Kjeldahl method. and the minerals by the AOAC standard procedure. The statistical analyzes for the experimental designs were performed in the SAS by the GLM procedure. The AMMI method is most suitable due to the graphical arrangement of both the genotypes and the environments and high correlation with others evaluated methods. The use of highly correlated methods is not recommended, as in the cases of Plaisted and Peterson and Wricke and the methods of Annicchiarico and Lin and Binnsthat show strong association and produce similar genotypic classifications. The use of one of them incombination with that of Eberhart and Russell or AMMI can add information to the stability analysis. Statistically significant differences in the genotype as well as in the genotype×environment interaction for minerals, proteins and grain yield were observed in all the assays. The lines presenting the highest protein contents showed the lowest grain yields, and it indicated the prominent “phenotypic cost” of protein in overall cowpea seed production. The methods by Eberhart and Russell, Lin and Binns and AMMI showed similar results for selection of superior genotypes. For the protein content, the lines C3Q, C3M, C2S and C1J presented grain yields equal to or greater than the general mean of the experiments and average of 27% of protein. For iron and zinc contents, the line C4I and T16_2R presented grain yield equal to or greater than the general mean of the experiments, with mean values of Fe and Zn 15% higher than the values of the evaluated cultivars. For the potassium and calcium contents, the C4I and C3O strains showed grain yield equal to or greater than the general average, with K and Ca means higher than the values of the cultivars evaluated. All the lines mentioned above presented broad adaptability and good stability in the series of evaluated environments showing great potential to be released as new cultivars for the Brazilian semiarid. Cooking had a reduced effect on protein, potassium, calcium, iron and zinc contents in the cowpea beans. The CPCR3F6L17 obtained high grain yield and high levels of protein, potassium, iron and zinc, after cooking, being promising for the region studied